Solidarność Walcząca . [biuletyn MK NSZZ "Solidarność" Ziemi Łódzkiej], no. 27, 1982 - Krasicki, Ignacy; Słodkowski, Wojciech; Dłużniewski, Jerzy; Lipski, Paweł; Niedbała, Andrzej (MKS NSZZ "Solidarność"], 1982)
Print run: 3000+60-7000 copies